2019
DOI: 10.1038/s41598-019-54589-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Heavy Metals in Herbal Food Supplements using Bismuth/Multi-walled Carbon Nanotubes/Nafion modified Graphite Electrodes sourced from Waste Batteries

Abstract: An electrochemical sensor based on graphite electrode extracted from waste zinc-carbon battery is developed. The graphite electrode was modified with bismuth nanoparticles (BiNP), multi-walled carbon nanotubes (MWCNT) and Nafion via the drop coating method. The bare and modified graphite electrodes were used as the working electrode in anodic stripping voltammetry for the determination of trace amounts of cadmium (Cd2+) and lead (Pb2+). The modified electrode exhibited excellent electroanalytical performance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…The electrodes were modified with bismuth nanoparticles and used in anodic stripping voltammetric technique for trace metal detection. The linear range was found to be 5 ppb to 1000 ppb with LODs of 1.06 ppb for Cd 2+ and 0.72 ppb for Pb 2+ (Palisoc, Vitto, & Natividad, 2019) .…”
Section: Other Types Of Sensorsmentioning
confidence: 94%
See 1 more Smart Citation
“…The electrodes were modified with bismuth nanoparticles and used in anodic stripping voltammetric technique for trace metal detection. The linear range was found to be 5 ppb to 1000 ppb with LODs of 1.06 ppb for Cd 2+ and 0.72 ppb for Pb 2+ (Palisoc, Vitto, & Natividad, 2019) .…”
Section: Other Types Of Sensorsmentioning
confidence: 94%
“…The electrochemical analysis showed good sensitivity towards detection and a stability up to 72 hours (W. Zhang, et al, 2020). Palisoc et al (2019) has also reported the use of a graphite based electrode extracted from a Zn battery towards the detection of Cd and Pb in trace amounts in herbal food supplements. The electrodes were modified with bismuth nanoparticles and used in anodic stripping voltammetric technique for trace metal detection.…”
Section: Other Types Of Sensorsmentioning
confidence: 95%
“…Palisoc et al [ 104 ] used discarded batteries to create a novel approach for detecting heavy metals in herbal dietary supplement samples using bismuth/multi-walled carbon nanotubes/nafion modified graphite electrodes. The crop-coating approach was used to modify the graphite electrode using bismuth nanoparticles (BiNP), multi-walled carbon nanotubes (MWCNT), and Nafion.…”
Section: Application Of Engineered Nanomaterialsmentioning
confidence: 99%
“…Due to the extreme toxicities, heavy metal ion pollution can be considered as a cause of serious health problem and environmental damage at their very low concentration. There is a series study of detection of heavy metal ions at trace levels such as mushroom‐derived carbon dots, 88 triple‐indicator‐based multidimensional colorimetric sensor platform, 89 atomically precise cluster−cellulose nanocrystal composites, 90 carbon nanotube composite electrodes, 91 and colorimetric sensors based on gold nanostructures 92,93 . Practical applications of identification of heavy metal ions utilizing nanosensor platform were demonstrated as a promising method to protect the environment and public health (Figure 3(c)).…”
Section: Hazardous Chemicalsmentioning
confidence: 99%